Odpowiedzi

Najlepsza Odpowiedź!
2010-01-13T17:58:56+01:00
A){x+y=9
{x-y=3

2x=12 /:2
x=6

x+y=9
x=6

6+y=9
x=6

y=9-6
x=6

y=3
x=6

b){3x+2y=2
{-3x+y=10

3y=12 /:3
y=4

3x+2y=2
y=4

3x+2*4=2
y=4

3x+8=2
y=4

3x=2-8
y=4

3x= -6 /:3
y=4

x=-2
y=4

c){3x+2y=2
{2x+2y=2 /*(-1)

3x+2y=2
-2x+-2y=-2

x=0

3x+2y=2
x=0

3*0+2y=0
x=0

0+2y=2
x=0

2y=2 /:2
x=0

y=1
x=0

d){x+4y=11 /*(-2)
{2x+5y=10

-2x-8y=-22
2x+5y=10

-3y=-12 /(-3)
y=-4

2x+5y=10
y=-4

2x+5*(-4)=10
y= -4

2x-20=10
y=-4

2x=10+20
y=-4

2x=30 /:2
y=-4

x=15
y=-4